Biosafety of Vibrio parahaemolyticus from vegetables based on antimicrobial sensitivity and RAPD profiling - Tunung, Robin; Jeyaletchumi, P.; Noorlis, A.; Tang, Y. H.; Sandra, A.; Ghazali, F. M.; Noranizan, Binti Mohd Adzahan; Lesley, Maurice Bilung; Haresh, K. K.; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Son, Radu (International Food Research Journal (IFRJ), 2012)
This study was undertaken to characterize the antibiotic resistance and randomly amplified polymorphic DNA (RAPD) profiles of Vibrio parahaemolyticus isolates from raw vegetable samples. A total of 46 isolates of V. parahaemolyticus recovered from raw vegetables samples and were confirmed by PCR were analyzed in this study. Most of the isolates were resistant to nalidixic acid (93.48%) and were the least resistant towards imipinem (4.35%). The MAR index results also demonstrated high individual and multiple resistances to antibiotics among the isolates. From the RAPD analysis, the size for RAPD fragments generated ranged from 250 bp to 1,500 bp, with most of the strains contained three major gene fragments of 350, 1,000 and 1,350 bp. The RAPD profiles revealed a high level of DNA sequence diversity within the isolates. Antibiotic resistance and RAPD proved to be effective tools in characterizing and differentiating the V. parahaemolyticus strains